Pulmonary Rhizopus arrhizus infection treated with high-dose liposomal amphotericin B in a heart transplant recipient under ECMO: a case report - Jiang, Wei; Zhai, Jinghui; Li, Boyu; Ma, Jie; Zhang, Sixi (Frontiers in Medicine, 2025)
Pulmonary mucormycosis caused by Rhizopus arrhizus is an emergent, fulminant threat in immunocompromised hosts, yet therapeutic success remains elusive when extracorporeal membrane oxygenation (ECMO) is required. While liposomal amphotericin B (L-AMB) is endorsed as first-line therapy, its pharmacokinetics are profoundly altered by ECMO—dilution, circuit sequestration, and impaired lung penetration all conspire to sub-therapeutic exposure. We report the first documented case in which these challenges were systematically overcome. A 52-year-old cardiac-transplant recipient, supported on veno-venous ECMO for refractory hypoxaemia, developed rapidly progressive pneumonia. Metagenomic next-generation sequencing (mNGS) of bronchoalveolar lavage fluid returned a definitive Rhizopus arrhizus signature within 24 h, prompting immediate escalation to high-dose L-AMB (10 mg/kg/day). Therapeutic drug monitoring confirmed sustained trough levels above 7 μg/mL despite a 3.5-fold increase in volume of distribution. Serial mNGS quantification demonstrated a logarithmic decline in fungal reads to undetectable levels by day 10, accompanied by radiological resolution and preserved renal function. After 28 days of intravenous therapy, the patient was discharged on oral isavuconazole with no relapse at 6 months. This case establishes that early pathogen identification by mNGS, coupled with aggressive L-AMB dose optimisation under rigorous pharmacokinetic guidance, can achieve cure of pulmonary mucormycosis even in the most pharmacologically hostile environment of ECMO support.